2018
DOI: 10.1093/cvr/cvy147
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes in hypertrophic cardiomyopathies: scientific update from the Working Group of Myocardial Function of the European Society of Cardiology

Abstract: Disturbed metabolism as a consequence of obesity and diabetes may cause cardiac diseases (recently highlighted in the cardiovascular research spotlight issue on metabolic cardiomyopathies).1 In turn, the metabolism of the heart may also be disturbed in genetic and acquired forms of hypertrophic cardiac disease. Herein, we provide an overview of recent insights on metabolic changes in genetic hypertrophic cardiomyopathy and discuss several therapies, which may be explored to target disturbed metabolism and prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 95 publications
2
60
0
1
Order By: Relevance
“…There is good evidence that HCM patients exhibit elevated metabolic activity and increased myocardial stiffness ( 6 , 24 , 45 47 ). We propose that the decrease in myocardial stiffness observed in AID-TAT treated cTnI-G203S mice, evidenced by reduced FS ( Table 1 ), may be associated with restored cytoskeletal organization ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There is good evidence that HCM patients exhibit elevated metabolic activity and increased myocardial stiffness ( 6 , 24 , 45 47 ). We propose that the decrease in myocardial stiffness observed in AID-TAT treated cTnI-G203S mice, evidenced by reduced FS ( Table 1 ), may be associated with restored cytoskeletal organization ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While classic models of HF are characterized by reduced ejection fraction, HCM is a paradigm of diastolic dysfunction with normal or even super-normal myocardial contractility. Consequently, any a priori assumption that the conclusions of prior studies on HF might be extended to HCM would have been arbitrary [4]. This is why we embarked on the present investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation can be demonstrated in approximately 60% of HCM patients and are considered causative [2,3]. A common cellular phenotype induced by HCM sarcomere mutations is an inefficient sarcomere contraction, which is attributed to diverse changes in sarcomere properties including increased myofilament Ca 2+ sensitivity and triphosphatase (ATPase) activity suggesting increased adenosine triphosphate (ATP) utilization [4]. This is consistent with in vivo studies using 31 P-magnetic resonance (MR) spectroscopy that have demonstrated impaired cardiac energetics under resting conditions and during exercise in patients with HCM [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, DCM caused by TTN gene variants has been linked with mitochondrial dysfunction and metabolic perturbations as cause of disease progression [ 19 ]. Overall, these studies indicate that timely disease stage-specific treatment of metabolic perturbations may slow down disease progression in cardiomyopathy patients [ 20 ]. An observational cohort to determine the predictive value of metabolic biomarkers (BIO FOr CARe: identification of biomarkers for development and progression of HCM in carriers of the Dutch MYBPC3 founder carriers) and a clinical trial using metabolic drug therapy aimed to improve energetics of the heart at preclinical stage in HCM gene variant carriers are currently being performed by several DOSIS principal investigators (ENERGY trial) [ 21 ].…”
Section: Altered Metabolism As Key Driver Of Disease In Cardiomyopathmentioning
confidence: 99%